Optimalisasi Kualitas Dokumentasi Asuhan Keperawatan dengan Pendekatan SOAP di Rawat Jalan Anak: Pilot Study - Elisabet Herlyani Bota Koten; Tuti Afriani; Sarvita Dewi; Aat Yatnikasari; Enie Novieastari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to find the root of the problem to streamline documentation in outpatient care. The method in this research is a case study using a particular pilot study approach for nurses in outpatient rooms for children through Kurt Lewin's theory of change. Problem analysis was performed using a fishbone. The implementation is carried out as a solution to the problems that occur in drafting a Standard Operating Procedure and a monitoring format for monitoring the evaluation of nursing care documentation using the SOAP approach and socializing innovation products. The research results with fishbone analysis showed that the quality of nursing care documentation using the SOAP approach in outpatient rooms for children was not up to standard. In conclusion, the root of the problem is identified. The implementation of a pilot study related to the optimization of the quality of nursing care documentation. Hospital X is at the stage of moving/movement change. Innovative products are socialized and accepted for further instrument testing. Keywords: Evaluation, Documentation Quality, Documentation Optimization